ANALISIS BEBAN KERJA PEGAWAI NEGERI SIPIL PADA SEKRETARIAT DINAS PEKERJAAN UMUM PERUMAHAN DAN ENERGI SUMBER DAYA MINERAL PROVINSI DIY (STUDI KASUS JABATAN FUNGSIONAL UMUM) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2021)
This research on the workload problem of Civil Servants is based on the number of Civil Servants who exceeds the number of public functional positions (JFU) at the Secretariat of the Office of Public Works, Housing and Energy of Mineral Resources of DIY Province, namely 13 general functional positions and with 29 employees Civil Affairs. The purpose of this study was to determine the suitability between workloads for existing job assignments and to find out the needs of Civil Servants needed to handle 13 general functional positions that have been established. This study uses a descriptive qualitative research design, using the Full-Time Equivalent (FTE) method. This method compares the amount of time the task is multiplied by the workload compared with the amount of effective work time. The results of this study indicate that there is a mismatch between workload on office duties and a shortage of employees in the general functional position of the Secretariat of the Office of Public Works, Housing and Energy of Mineral Resources of DIY Province. This is indicated by the normal workload in general functional positions as much as 13 employees or 45% of the normal amount of 100% but there are still general functional positions where the workload is underloaded by 9 employees or 31% of the normal amount and 7 employees are overloaded or 21% of the total normal. While the number of employees to handle 13 general functional positions is 29 Civil Servants, according to the results of the analysis for future staffing planning, it is necessary to optimize employee performance by changing the composition of the workforce by adding 4 Civil Servants to 33 Civil Servants.
Keywords: Analysis; Methods; Workload; Employees